2016
DOI: 10.1167/iovs.15-18473
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Changes in the Choriocapillaris, Choroidal Vessels, and Retinal Morphology After Focal Laser Photocoagulation Using OCT Angiography

Abstract: Optical coherence tomography angiography can be used to visualize choriocapillaris alterations associated with focal laser photocoagulation treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…The exclusion criteria were the presence of other chorioretinal diseases, glaucoma or ocular hypertension; an axial length shorter than 22.0 mm or longer than 26.0 mm; intraretinal or preretinal hemorrhages or hard exudates with diameters larger than one-third of the disc diameter within the central 3 × 3-mm square on the color fundus photograph; a history of any intervention for macular lesions; intraocular surgery other than cataract extraction; and cataract surgery within 6 months of study enrollment. We excluded eyes with a history of photocoagulation of the macular area because the decorrelation signals in the choriocapillaris layer were attenuated after this treatment 49 . To guarantee image quality, we also excluded eyes with a signal strength index (SSI) score of 60 or less 50 .…”
Section: Methodsmentioning
confidence: 99%
“…The exclusion criteria were the presence of other chorioretinal diseases, glaucoma or ocular hypertension; an axial length shorter than 22.0 mm or longer than 26.0 mm; intraretinal or preretinal hemorrhages or hard exudates with diameters larger than one-third of the disc diameter within the central 3 × 3-mm square on the color fundus photograph; a history of any intervention for macular lesions; intraocular surgery other than cataract extraction; and cataract surgery within 6 months of study enrollment. We excluded eyes with a history of photocoagulation of the macular area because the decorrelation signals in the choriocapillaris layer were attenuated after this treatment 49 . To guarantee image quality, we also excluded eyes with a signal strength index (SSI) score of 60 or less 50 .…”
Section: Methodsmentioning
confidence: 99%
“…This study showed changes in the choriocapillaris on manually segmented images, but, in most cases, there were no changes in the superficial or deep retinal vasculature in the region of focal laser. In some cases, there were changes in the outer plexiform layer on OCT structural scans (Cole, Novais et al 2016). OCT-based studies have also suggested that focal laser does not significantly alter the anatomy of the inner retina (Bolz, Kriechbaum et al 2010), but histologic studies performed on monkey models of focal laser injury to the retina (Wilson, Finkelstein et al 1988) demonstrate decreased capillary density in the region of focal laser.…”
Section: Review Of Clinical Studies Utilizing Octamentioning
confidence: 99%
“…Due to a high concentration of melanin, which absorbs a great deal of the energy, the RPE is the main target of laser photocoagulation [9]. Considering that the choriocapillaris is adjacent to the RPE and the melanin in the choroidal stroma can also absorb the laser energy, the choriocapillaris is likely to be affected by laser photocoagulation.…”
Section: Introductionmentioning
confidence: 99%
“…Although indocyanine green angiography (ICGA) is often used to evaluate the choroidal microcirculation, it is sometimes difficult to visualize the blood flow in the choriocapillaris due to rapid leakage of the ICG dye from the choriocapillaris that then stains Bruch's membrane and the choroidal stroma [15,16]. Optical coherence tomography angiography (OCTA) is a new imaging technology that provides depth-resolved visualization of the retinal microvasculature and the choriocapillaris without the need for dye injection [9,[15][16][17][18]. It performs multiple repeated B-scans in the same retinal area to differentiate the moving erythrocytes in the vasculature from the static fundus structure [15,17].…”
Section: Introductionmentioning
confidence: 99%